High-Capacity and Dispersionless Delay Lines Based on Plasmonic Waveguide Periodically Coupled With Bilaterally Located Ring and Slot Resonators - Qi Lu; Qiang Liu; Wei Jiang; Jinsong Xia; Qingzhong Huang (IEEE Photonics Journal)
We propose and study optical delay lines with high capacity and low dispersion based on a plasmonic waveguide periodically coupled with bilaterally located ring and slot resonators. The repetitive unit exhibits plasmon-induced transparency (PIT) with a large delay-bandwidth product due to the interference between the two-mode ring and single-mode slot resonators. By choosing appropriate parameters, the cascaded PIT units can possess a broad transparency window with moderate fluctuations and produce wideband dispersionless slow light. A theoretical model is developed to analyze the proposed structure and the results are validated by finite-difference time-domain simulations. The pulse propagation results indicate that the spectral fluctuations have a negligible effect on the delayed pulse shape. Using multiple cascaded PIT units, we demonstrate that the group index of the waveguide approaches 36, the 3-dB bandwidth is larger than 21 nm, and a storage efficiency of 0.5 bit/unit can be realized with negligible distortion. Due to the high performance, the proposed delay line may find potential applications in future nanoscale integrated photonic systems.